Evolving therapeutic landscape of immunoglobulin A nephropathy: targeted immune pathways and novel therapies - Yaerim Kim (Kidney Research and Clinical Practice, 2026)
Recent advances in the understanding of immunoglobulin A nephropathy (IgAN) pathogenesis have led to a rapidly expanding therapeutic landscape for the condition. Treatments have historically relied on optimized supportive care aimed at controlling blood pressure and reducing proteinuria through blockading of the renin-angiotensin system and inhibition of the sodium glucose cotransporter 2. Growing insights into immune dysregulation, mucosal immunity, complement activation, and maladaptive hemodynamic responses have facilitated the development of multiple disease-targeting therapies for IgAN. These include agents that modulate mucosal immune responses, inhibit APRIL (a proliferation-inducing ligand) and BAFF (B-cell activating factor) signaling, block complement activation, or target endothelin-mediated pathways. Several of these therapies have shown promising antiproteinuric and kidney-protective effects in clinical trials. This review summarizes recent advances in the treatment of IgAN, with a particular focus on therapies targeting disease-specific pathogenic drivers and their implications for future therapeutic strategies.